Tetanus prophylaxis in superficial corneal abrasions. Issue 1 (1st January 2003) - Mukherjee, Prodeep; Sivakumar, A; Mackway-Jones, K
Abstract : A short cut review was carried out to establish whether tetanus prophylaxis is indicated after non-penetrating corneal abrasion. Altogether 30 papers were found using the reported search, of which one presented the best evidence to answer the clinical question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of this best paper are tabulated. A clinical bottom line is stated.